2018
DOI: 10.1016/j.disopt.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Discrete convexity in joint winner property

Abstract: In this paper, we reveal a relation between joint winner property (JWP) in the field of valued constraint satisfaction problems (VCSPs) and M ♮ -convexity in the field of discrete convex analysis (DCA). We introduce the M ♮ -convex completion problem, and show that a function f satisfying the JWP is Z-free if and only if a certain function f associated with f is M ♮ -convex completable. This means that if a function is Z-free, then the function can be minimized in polynomial time via M ♮ -convex intersection a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A binary VCSP function F satisfying the joint winner property can be transformed to a function represented as the sum two special M-convex functions of the form (1) with an infinite quadratic coefficient. This fact explains the polynomial-time solvability of F (see [6] for details). The class of functions represented as the sum of two general quadratic M-convex functions corresponds to a new tractable class of binary VCSPs.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A binary VCSP function F satisfying the joint winner property can be transformed to a function represented as the sum two special M-convex functions of the form (1) with an infinite quadratic coefficient. This fact explains the polynomial-time solvability of F (see [6] for details). The class of functions represented as the sum of two general quadratic M-convex functions corresponds to a new tractable class of binary VCSPs.…”
Section: Introductionmentioning
confidence: 84%
“…Quadratic Mconvex functions have a close relationship with tree metrics [5], which is an important concept for mathematical analysis in phylogenetics (see e.g., [12]). Recently, Iwamasa-Murota-Živný [6] have revealed hidden quadratic M-convexity in valued constraint satisfaction problems (VCSPs) with joint winner property [2], and presented a perspective to their polynomial-time solvability from discrete convex analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if F satisfies the JWP, then F can be minimized in polynomial time. Furthermore, Iwamasa, Murota, and Živný [20] revealed that Z-free instances are quadratic M 2 -representable.…”
Section: Related Workmentioning
confidence: 99%
“…Various kinds of submodularity induce tractable classes of language-based VCSP instances [22], and a larger class of such submodularity can be understood as L-convexity on certain graph structures [14]; see also [15]. On the other hand, Iwamasa, Murota, and Živný [20] have pointed out that M-convexity plays a role in hybrid VCSPs. They revealed the reason for the tractability of a VCSP instance satisfying the JWP from a viewpoint of M-convexity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation